Utilization of PVP-PLA Combination in Fabricating Theophylline-loaded Filament for 3D Printing with Immediate Release Behavior - Kurniawan, Arief; Surini, Silvia (UI Scholars Hub, 2023)
Fused deposition modeling (FDM), known as a highly effective 3D printing technique, holds promise as an alternative approach to tablet manufacturing. While commonly employing thermoplastic polymers as starting materials, the integration of established pharmaceutical excipients remains unexplored. Polyvinyl pyrrolidone (PVP) is a frequently used excipient known for its potential to confer immediate-release properties to drugs. However, its suitability for extrusion is hindered by its thermal and melt-rheological properties. In contrast, polylactic acid (PLA), which has robust mechanical strength and thermal plasticity, was expected to overcome PVP’s limitations. This study aims to obtain drug-loaded filaments using the combination of PVP and PLA through a hot-melt extrusion process, aiming for favorable mechanical properties and immediate-release behavior. Utilizing a twin-screw extruder, and theophylline was used as the model drug, three formulations were optimized –FP1, FP2, and FP3– containing 0%, 10%, and 20% theophylline, respectively. Subsequent evaluation including filament morphology, mechanical properties, drug content, and drug release profile, were performed to each filament. FP2 emerged as the most promising formulation, with 10.35% (w/w) drug load and over 95% drug released in an hour. All formulations exhibited slightly rough filament surfaces with diameters averaging 1.4-1.6 mm. Notably, an increase in the theophylline content correlates with the diminished filament strength, evident in reduced hardness and a rise in brittleness. This study emphasized the potential of PVP-PLA-based filaments for future pharmaceutical 3D printing formulations, providing immediate drug release characteristics.